Volumetric and acoustic study of aqueous binary mixtures of quinine hydrochloride, guanidine hydrochloride and quinic acid at different temperatures. (February 2015) - Dhondge, Sudhakar S.; Shende, Pritam H.; Paliwal, Lalitmohan J.; Deshmukh, Dinesh W.
Abstract : Graphical abstract: Highlights: Volumetric and compressibility properties of important drugs have been reported. κ ϕ 0 values for studied systems are negative at studied temperatures. Quinic acid, guanidine hydrochloride act as structure breaker and quinine hydrochloride acts as maker. Abstract: In the present communication, we report the fundamental thermodynamic properties like volumetric and compressibility of very important bioactive compounds, viz. quinine hydrochloride, guanidine hydrochloride and quinic acid (0.01 to 0.1) mol · kg −1 in water at temperatures T  = (278.15, 288.15 and 298.15) K. The experimental values of density ( ρ ) of aqueous solutions and speed of sound ( u ) in aqueous solutions of the above compounds within the concentration range (0.01 to 0.1) mol · kg −1 have been obtained. The apparent molar volumes ( Vϕ ), and apparent molar isentropic compressibilities ( κϕ ) of quinine hydrochloride, guanidine hydrochloride and quinic acid in water have been computed at three different temperatures. Speed of sound values have also been used to calculate the hydration number ( nH ) of the solute. The temperature dependence of the apparent molar volume has been used to calculate the thermal expansion coefficient ( α ∗ ), apparent molar expansivity ( E ϕ 0 ) and Hepler's constant ∂ 2 V ϕ 0 / ∂ T 2 . The derived parameters have been used to interpret the results in terms of (solute + solute)/(ion + ion), (solute + solvent) interactions, structure making and structure breaking tendencies of solutes in water.